2015
DOI: 10.1093/jnci/djv041
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Amplified and Overexpressing Glioblastomas and Association With Better Response to Adjuvant Metronomic Temozolomide

Abstract: EGFR-amplified/overexpressing glioblastomas strongly benefit from metronomic temozolomide-based therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 28 publications
1
27
1
Order By: Relevance
“…In contrast, MGMT promoter methylation was not prognostic in the subgroup of patients with EGFRvIII-positive glioblastomas. However, we could not confirm the suggestion of a prognostic interaction between EGFRvIII expression and MGMT promoter methylation in a published data set of 13 patients with EGFRvIII-positive tumors and available MGMT promoter methylation status (16), and in the large ACT IV phase III data set (46).…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…In contrast, MGMT promoter methylation was not prognostic in the subgroup of patients with EGFRvIII-positive glioblastomas. However, we could not confirm the suggestion of a prognostic interaction between EGFRvIII expression and MGMT promoter methylation in a published data set of 13 patients with EGFRvIII-positive tumors and available MGMT promoter methylation status (16), and in the large ACT IV phase III data set (46).…”
Section: Discussioncontrasting
confidence: 85%
“…Individual studies suggested that these alterations are associated with shorter overall survival (OS) among anaplastic astrocytoma patients (12) and glioblastoma patients (11), while other authors found a prognostically favorable role of EGFRvIII positivity in glioblastoma patients (16). Yet other studies, including previous publications of the German Glioma Network (13,17), as well as a recent meta-analysis of eight publications (18), did not confirm a distinct prognostic role of EGFR amplification and EGFRvIII positivity, although a trend toward decreased long-term survival with EGFRvIII-positive glioblastoma has been reported (13,19,20).…”
Section: Introductionmentioning
confidence: 99%
“…To demonstrate the specificity and cellular effects in vitro and in vivo, we used the human derived glioblastoma (GBM) cell line U-87 MG. We recorded the magnetic field signals of siRNA oligonucleotide molecule for the epidermal growth factor receptor (EGFR) gene, which plays a key role in cancer biology [9][10][11][12][13]. Here we show that we can specifically knock down EGFR gene expression, with resulting biological effects, in human U-87 MG and primary (GBM) cells by exposing these cells to physical-EGFR siRNA and RFE-siEGFR signal.…”
Section: Introductionmentioning
confidence: 94%
“…The constitutively active mutant EGFRvIII, which is also known as de2-7 EGFR or DEGFR, is present in 25%e30% of GBMs with concurrent EGFR amplification/overexpression [30,31]. EGFR amplification is observed in most (97%) Classical subtype gliomas but is infrequently observed in other subtypes.…”
Section: Egfrviii Amplificationmentioning
confidence: 99%